Some Of Time Management Methods And Its Relationship With Administrative Innovation In Msila Sport Complexes. - برباخ رابح; أوشن بوزيد (sports creativity, 2025)
Abstract: this study entitled " time management methods and its relation with administrative innovation in sport complexes", aims to discuss whether or not time management(the independent variable) have a relationship with administrative innovation (the dependant variable) in Msila sport complexes, and to determine whether or not time management important for sport complexes agents practice, and to determine their administrative innovation degree, and on other hand, to examined the nature of the relationship between participative management and self management methods as two methods of time management, and measure its relationship with administrative innovation in sport complexes. The researcher used the descriptive methodology and made use of questionnaire to gather data on a random sample of administration agents working in Msila sport complexes. This study calculated 112 agents out of 266 agents which represent our study population. The study proof that there is a high level degree of time management methods and administrative innovation in sport complexes and the methods of participative management and self management as two methods of time management rang to administrative innovation in sport complexes. Keywords: Time mangement- Participative management- Self management-Administrative innovation